Índice de desarrollo humano y eventos de salud pública: revisión sistemática de la literatura 1990-2015 - Luis Felipe Higuita-Gutiérrez; Jaiberth Antonio Cardona-Arias (Universidad de Antioquia, 2018)
Objective: Systematize scientific publications that describe the relationship of the human development index and morbidity and mortality indicators caused by communicable and noncommunicable diseases. Methodology: A systematic review of 6 multidisciplinary databases research studies that report correlation, regression or determination coefficients in the human development index of the United Nations program for development and morbidity or mortality for healthcare events. Results: 21 studies that evaluated the relation between human development and more than 35 events of interest in public health were identified. Neoplastic diseases (except breast and ovarian cancer) and communicable diseases presented inverted correlations with an index ranging from -0.85 to -0.40. Suicide, physical inactivity, drug use, breast cancer and ovarian cancer presented direct correlations ranging from 0.27 to 0.89. This study identified that the index constitutes an excellent predictor regarding the occurrence of tuberculosis, suicide and malaria. Conclusion: The study evidenced that human development paralleled the best health conditions represented by a decrease in morbidity and mortality resulting from cancer and communicable diseases; this shed a light so that countries with a low development index do not delay socially important Investments because of a lack of resources. They should invest simultaneously in economic dimensions and social services, particularly promoting health care and basic education